2013
DOI: 10.1002/anie.201306230
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Optical Detection of Stabilized Artificial G‐Quadruplexes Under Confined Conditions

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Therobustness of the pores is strengthened by synergistic hydrophobic interactions between the lateral CH 3 -(CH 2 ) 3,11 -a nd central -(CH 2 ) 6,8 -c hains,a lternatively connecting with each other between each quartet level and forming ah ydrophobic and protective shell for the channels.F rom single-crystal X-ray data of the T-quartet channels reported here,i tc an be concluded that:1)two anions can be recognized by individual T-quartets through synergistic hydrogen bonding/ion pairing; 2) Complementary anion-p stacking between triazole rings and anions from two different successive T-quartets,enabling acolumnar T-quartet organization and achieving an anion-p slide channel shaped pathway for anion translocation;3 )the T-quartet for anion channels are reminiscent of the previously reported imidazole I-quartet for water channels [33][34][35] and the Guanosine G-quartet for K + channels. [36][37][38] The 1 HNMR and MS data (see Figures S1-S22 and the Supporting Information) of all synthesized compounds are in agreement with the proposed formulas.T he 1 HNMR spectra of protonated TH + C4·X À (Figure 3a), TH + C12·X À (see Figure S1), and [TH + C8TH + ]·2 X À (see Figure S2;X À = Cl À ,Br À , I À and NO 3 À )i ndicated as table downfield shift of about 0.75 ppm of the H1 in the triazole ring after protonation, and is indicative of strong hydrogen bonding with X À and reminiscent of the presence of the dissociated salt in aqueous solution for all the studied anions.F or [TH + C6TH + ]·2 X À (Figure 3b)w eo bserved am aximum downfield shift of Dd % 0.75 ppm for the NO 3 À ,while upfield shifted (Dd = À0.05 to À0.3 ppm) peaks relative to the NO 3 À are observed for the other anions Cl À ,Br À ,I À ,suggesting their close proximity to the triazole moiety.…”
Section: Figure 1) or Two Apical Sites Of As Andwiched Anionsupporting
confidence: 80%
“…Therobustness of the pores is strengthened by synergistic hydrophobic interactions between the lateral CH 3 -(CH 2 ) 3,11 -a nd central -(CH 2 ) 6,8 -c hains,a lternatively connecting with each other between each quartet level and forming ah ydrophobic and protective shell for the channels.F rom single-crystal X-ray data of the T-quartet channels reported here,i tc an be concluded that:1)two anions can be recognized by individual T-quartets through synergistic hydrogen bonding/ion pairing; 2) Complementary anion-p stacking between triazole rings and anions from two different successive T-quartets,enabling acolumnar T-quartet organization and achieving an anion-p slide channel shaped pathway for anion translocation;3 )the T-quartet for anion channels are reminiscent of the previously reported imidazole I-quartet for water channels [33][34][35] and the Guanosine G-quartet for K + channels. [36][37][38] The 1 HNMR and MS data (see Figures S1-S22 and the Supporting Information) of all synthesized compounds are in agreement with the proposed formulas.T he 1 HNMR spectra of protonated TH + C4·X À (Figure 3a), TH + C12·X À (see Figure S1), and [TH + C8TH + ]·2 X À (see Figure S2;X À = Cl À ,Br À , I À and NO 3 À )i ndicated as table downfield shift of about 0.75 ppm of the H1 in the triazole ring after protonation, and is indicative of strong hydrogen bonding with X À and reminiscent of the presence of the dissociated salt in aqueous solution for all the studied anions.F or [TH + C6TH + ]·2 X À (Figure 3b)w eo bserved am aximum downfield shift of Dd % 0.75 ppm for the NO 3 À ,while upfield shifted (Dd = À0.05 to À0.3 ppm) peaks relative to the NO 3 À are observed for the other anions Cl À ,Br À ,I À ,suggesting their close proximity to the triazole moiety.…”
Section: Figure 1) or Two Apical Sites Of As Andwiched Anionsupporting
confidence: 80%
“…The robustness of the pores is strengthened by synergistic hydrophobic interactions between the lateral CH 3 ‐(CH 2 ) 3,11 ‐ and central ‐(CH 2 ) 6,8 ‐ chains, alternatively connecting with each other between each quartet level and forming a hydrophobic and protective shell for the channels. From single‐crystal X‐ray data of the T‐quartet channels reported here, it can be concluded that: 1) two anions can be recognized by individual T‐quartets through synergistic hydrogen bonding/ion pairing; 2) Complementary anion‐π stacking between triazole rings and anions from two different successive T‐quartets, enabling a columnar T‐quartet organization and achieving an anion–π slide channel shaped pathway for anion translocation; 3) the T‐quartet for anion channels are reminiscent of the previously reported imidazole I‐quartet for water channels and the Guanosine G‐quartet for K + channels …”
Section: Methodsmentioning
confidence: 56%
“…2a) shifts to lower wavenumbers (Fig. 2b), 17,32 and the band at 1493 cm −1 (Fig. 2a) assigned to the imidazole ring N-7-C-8 stretching and C-8-H bending exhibits a slight shift to lower wavenumbers (Fig.…”
Section: Ft-ir Analysismentioning
confidence: 96%
“…31 Previous reports also showed that guanosine ribbons were successfully confined within mesoporous silica, 29 and artificial G-quadruplexes were stabilized and detected under confinement within a scaffolding of porous silica matrices. 32 Therefore, the above burgeoning achievements inspired us to use Sr 2+ based G-quadruplexes to synthesize other types of porous materials in a facile and economic way, as this avoids the use of a high concentration of GMP and divalent cations. In this work, nanotubes with different sizes of mesopores in the outer wall were fabricated, and some of these pore channels run perpendicularly to the center axis of the tube.…”
Section: Introductionmentioning
confidence: 99%